Multi-Perspective Characterization of a Performance of a Barrel Drill Made of Tungsten Carbide Composite - Rychlik, Kazimierz; Bramowicz, Mirosław; Kulesza, Sławomir (Materials, 2025)
This paper presents the results of an estimation of the structural and roughness parameters of the outer surface layers of a barrel drill made of cobalt matrix sintered tungsten carbide samples (WC-Co) made by sintering and subjected to finishing by grinding. In order to evaluate the geometric and functional structure of the surface, profilometric measurements were carried out at different scan lengths. The geometric structure of the studied surfaces was characterized by the roughness parameters Ra, Rq, and Rz, while the functional structure was determined by the reduced profile heights Rpk, Rk, Rvk and the material ratios M and M determined by the Abbott-Firestone curves. Multiscale analysis of the dependence of the roughness and functional parameters on the measurement lengths was carried out using the root mean square (RMS) method, from which monofractal structures of the surface profile variations were found. Consistency of the fractal dimensions estimated for the drill bit might be due to its finer finishing.